Reflection of the Critical Theory, Revolutionary Pedagogy and Liberating Education - Cifuentes Medina, José Eriberto; Moreno Pinzón, Israel Alfonso; Camargo Silva, Aura Lucía (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The research makes an analysis of critical theory from Horkheimer, the revolutionary pedagogy proposed by Peter McLaren and liberating education in the perspective of Paulo Freire, contributes to breaking down the meaning of education in the twentieth century and its projection in the XXI century. Objective: To identify the main factors of incidence in education and pedagogy based on Horkheimer, Peter McLaren and Paulo Freire. Method: The study responds to a qualitative approach and responds to a documentary review in relation to the factors related to the historical epoch, such as the contributions of the Frankfurt School, the violent but also peaceful revolution in different areas of world society and that has permeated all environments. Results: There is a historical and geographical journey through Europe, North America and South America of the three authors and, there are elements in common in favor of pedagogy and education, where man appears as the center of the educational process in search of a a healthy revolution of the mind and an education that frees it from the bondage of ignorance.